NEETs civic and political participation in outermost islands: The mediating roles of sense of community and agency - Simões, F.; Fernandes-Jesus, M.; Marta, E. (Journal of Community and Applied Social Psychology, 2022)
Our aim is to test the associations between collectivism, social support, sense of community, as well as agency with civic and political participation levels of NEETs living in The Azores, a group of islands forming a small and outermost archipelago. We surveyed 332 participants (M = 26.78; 69.30% women). We found that all factors, except for social support, were associated with higher participation levels among NEETs. We also found that stronger sense of community and agency mediated the connection between stronger collectivism and higher levels of participation. Therefore, we conclude that setting emotional bonds with the community and being involved in local traditions and causes are necessary conditions to translate dominant local values into NEETs civic and political participation in outer- most islands. We further discuss how these results can be translated into more effective, person-centred policies to support NEETs inclusion.